Pemberdayaan Ekonomi Berbasis Masjid dan Manajemen Ketakmiran pada Masjid An Nur dan FORSIMAL, Dadung, Mantingan - Mufti Afif; Andi Triyawan; Royyan Ramdhani Djayusman (University of Darussalam Gontor, 2017)
The purpose of outreach activities with the title of “ The Administrators Empowerment An Nur Dadung Mosque in the administrator’s management is to help the mosque administrators as the responsible to manage all activities and routines which connected for ummah on the religious, education and economics”. The second purpose, is to improve the scientific religion administrators An Nur Dadung mosque. To achieve the purpose of outreach has been implemented by a lecturer team faculty of economic and management, University of Darussalam Gontor, the outreach activities is conducted in the form of management training, discussion, and administrators supervision activities. From the outreach activities carried out by An Nur Dadung mosque, Mantingan, Ponorogo it can be concluded that an increase in the participation of society on activities conducted by An Nur mosque administrators. The existence of thought between a members of An Nur mosque administrators in fostering the community of this mosque. There’s no mosque administrators thought an old fashioned (jumud) and blamed another communities in terms of believed (madzhab).The next holding the investigation in Sunday morning between mosque each monthly with a doorprize from muhsinin and breakfast together.